Maintaining the Quality of Health Services in the New Normal Era: From Visit to Virtual - Dewi, Luh Gede Rusmaya; Gorda, Anak Agung Ngurah Oka Suryadinatha; Martini, Ida Ayu Oka (Jurnal Economia, 2024)
AbstractThe COVID-19 pandemic has forced hospitals to implement innovative steps to support the Indonesian government's large-scale social restriction program by moving from visits to virtual services via telemedicine. This study aims to analyze and explore the quality of telemedicine-based health services in the new normal era and explore other unique aspects of it. This study uses a qualitative research design with a phenomenological approach focusing on HaloKIH telemedicine services at Kasih Ibu Saba Hospital. Data collection techniques through interviews with data analysis technique used are the interactive model, namely data conduction, data display, and verification. The results showed that the quality of HaloKIH's telemedicine service was considered very good because it had been able to adapt the criteria from the E-ServQual dimension, namely efficiency, fulfillment of needs, reliability, privacy, responsiveness, compensation, and contact. The new unique dimension that emerges is the adaptation of the local wisdom of the surrounding culture.  Keywords:E-Service Quality, Health Service Quality, Telemedicine, New Normal